TiFe0.85Mn0.05 alloy produced at industrial level for a hydrogen storage plant. (12th August 2022) - Barale, Jussara; Dematteis, Erika M.; Capurso, Giovanni; Neuman, Bettina; Deledda, Stefano; Rizzi, Paola; Cuevas, Fermin; Baricco, Marcello
Abstract: Moving from basic research to the implementation of hydrogen storage system based on metal hydride, the industrial production of the active material is fundamental. The alloy TiFe0.85 Mn0.05 was selected as H2 -carrier for a storage plant of about 50 kg of H2 . In this work, a batch of 5 kg of TiFe0.85 Mn0.05 alloy was synthesized at industrial level and characterized to determine the structure and phase abundance. The H2 sorption properties were investigated, performing studies on long-term cycling study and resistance to poisoning. The alloy absorbs and desorbs hydrogen between 25 bar and 1 bar at 55 °C, storing 1.0H2 wt.%, displaying fast kinetic, good resistance to gas impurities, and storage stability over 250 cycles. The industrial production promotes the formation of a passive layer and a high amount of secondary phases, observing differences in the H2 sorption behaviour compared to samples prepared at laboratory scale. This work highlights how hydrogen sorption properties of metal hydrides are strictly related to the synthesis method. Graphical abstract: Image 1 Highlights: TiFe0.85 Mn0.05 alloy was prepared at industrial level and deeply characterized. Industrial preparation strongly affects the hydrogen sorption properties. TiFe0.85 Mn0.05 shows suitable properties for a large-scale storage system. TiFe0.85 Mn0.05 is activated in mild conditions, stable over cycling and poisoning.